Synthesis, characterization, and performance analysis of carbon molecular sieve-embedded polyethersulfone mixed-matrix membranes for the removal of dissolved ions - Qadir, D. (John Wiley and Sons Inc, 2020)
The asymmetric polyethersulfone (PES-15Â wt.) mixed-matrix membranes were prepared by incorporation of carbon molecular sieve (CMS) with varying concentrations (1, 3, and 5Â wt.). Physicochemical characterization of synthesized membranes was carried out using field emission scanning electron microscope, atomic force microscopy, contact angle, thermogravimetric analysis, zeta potential analyzer, porosity, and mean pore sizes. Performance analysis of synthesized mixed-matrix membranes was carried out by varying the operating parameters such as pressure (2â10Â bar), feed concentration (100â1,000Â mg/L), and cations type (Na+, Ca2+, Mg2+, and Sn2+). Effect of operating parameters and CMS concentration was investigated on pure water flux (PWF), permeate flux, and rejection of membranes. It was found that mixed-matrix membrane containing 15Â wt. PES with 1Â wt. CMS displayed the superior physicochemical characteristics in terms of hydrophilicity (37.9Â°), surface charge (â13.8Â mV), mean pore diameter (6.04Â nm), and thermal properties (TgÂ =Â 218.5Â°C), and overall performance. E5C1 membrane showed 1.5 times higher PWF (75.5Â LÂ mâ2Â hrâ1) and incremented in rejection for all salts than the nascent membrane. Practitioner points: Carbon molecular sieve-embedded mixed-matrix membranes were synthesized by phase inversion method. The resultant membranes experienced improved hydrophilicity, roughness, surface charge, porosity, and mean pore diameter with 1Â wt. CMS loading. The pure water flux was improved from 55.77 to 75.05Â LÂ mâ2Â hrâ1 when 1Â wt. CMS was added in pure PES. The observed rejection of a mixed-matrix membrane with 1Â wt. CMS was the maximum for all salts. Â© 2020 Water Environment Federation